An Adaptive Characterization of Signed Systems for Paraconsistent Reasoning - Batens, Diderik; Meheus, Joke; Provijn, Dagmar (2006)
In this paper we characterize the six (basic) signed systems from \cite{B&S:sspr} in terms of adaptive logics. We prove the characterization correct and show that it has a number of advantages.